Research Progress on the Role of Microglia Membrane Proteins or Receptors in Neuroinflammation and Degeneration - Zhao, Jun-Feng; Ren, Tong; Li, Xiang-Yu; Guo, Tian-Lin; Liu, Chun-Hui; Wang, Xun (Frontiers in Cellular Neuroscience, 2022)
Microglia are intrinsic immune cells of the central nervous system and play a dual role (pro-inflammatory and anti-inflammatory) in the homeostasis of the nervous system. Neuroinflammation mediated by microglia serves as an important stage of ischemic hypoxic brain injury, cerebral hemorrhage disease, neurodegeneration and neurotumor of the nervous system and is present through the whole course of these diseases. Microglial membrane protein or receptor is the basis of mediating microglia to play the inflammatory role and they have been found to be upregulated by recognizing associated ligands or sensing changes in the nervous system microenvironment. They can then allosterically activate the downstream signal transduction and produce a series of complex cascade reactions that can activate microglia, promote microglia chemotactic migration and stimulate the release of proinflammatory factor such as TNF-α, IL-β to effectively damage the nervous system and cause apoptosis of neurons. In this paper, several representative membrane proteins or receptors present on the surface of microglia are systematically reviewed and information about their structures, functions and specific roles in one or more neurological diseases. And on this basis, some prospects for the treatment of novel coronavirus neurological complications are presented.